2002
DOI: 10.17221/4412-pse
|View full text |Cite
|
Sign up to set email alerts
|

Aluminium induced acid phosphatase activity in roots of Al-sensitive and Al-tolerant barley varieties

Abstract: In barley roots significant increase of acid phosphatase activity was observed during Al treatment. Especially steep increase was found in the roots of Al-sensitive cv. Alfor treated with Al in the range of 1-10mM which was followed by sudden decline when higher concentration (10-100mM) was applied. Continual, but significantly lower increase in phosphatase activity was also demonstrated in the roots of Al-tolerant cv. Bavaria in the range of 1-50mM Al. In both cases, Al-induced increase of acid phosphatase ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…Therefore, our study upholds the view that one of the initial responses of plants to P deficiency stress is an increase in root acid phosphatase activity (Goldstein et al 1988, Duff et al 1994 because its function is the hydrolysis of inorganic phosphorous (Pi) from orthophosphate monoesters used for plant nutrition in the soil (Huttová et al 2002). Further, the findings of the present study is in accordance with Sukhada (1992) who reported higher acid phosphatase activity in comparison to alkaline phosphatase activity in roots of 4-month-old papayas inoculated with Glomus mosseae (Nicol.…”
Section: Discussionsupporting
confidence: 84%
“…Therefore, our study upholds the view that one of the initial responses of plants to P deficiency stress is an increase in root acid phosphatase activity (Goldstein et al 1988, Duff et al 1994 because its function is the hydrolysis of inorganic phosphorous (Pi) from orthophosphate monoesters used for plant nutrition in the soil (Huttová et al 2002). Further, the findings of the present study is in accordance with Sukhada (1992) who reported higher acid phosphatase activity in comparison to alkaline phosphatase activity in roots of 4-month-old papayas inoculated with Glomus mosseae (Nicol.…”
Section: Discussionsupporting
confidence: 84%
“…Supernatant was taken for enzyme assay. A standard curve was prepared with the known enzyme samples, and absorbances were taken at 322 nm following Huttova' et al (2002). The data presented were the average of 20 readings for each plant of each location, and standard errors were also depicted in the Figures.…”
Section: 2)mentioning
confidence: 99%
“…Glucosidase, phosphatase and protease activity was found mainly in the protein bodies and spherosomes of ungerminated seeds (Adams and Novellie 1975), however phosphatase and esterase activity was reported also from the testa of ungerminated wheat grains (Price and Ey 1970). In our previous work we reported the significant increase in acid phosphatase in barley roots during Al treatment (Huttová et al 2002). In contrast Al at 8mM concentration markedly inhibited the release of acid phosphatase from imbibiting barley grains.…”
Section: Toxic Effects Of Aluminium On Plants As Well As Mechanisms Omentioning
confidence: 86%